Galectin-3, a novel endogenous TREM2 ligand, detrimentally regulates inflammatory response in Alzheimer's disease. - Boza-Serrano, Antonio; Ruiz, Rocio; Sánchez-Varo, Raquel María; García‑Revilla, Juan; Yang, Yiyi; Jiménez-Ferrer, Itzia; Paulus, Agnes; Wennström, Malin; Vilalta, Ana; Allendorf, David; Dávila-Cansino, José Carlos; Stegmayr, John; et al. (Springer, 2019)
Alzheimer's disease (AD) is a progressive neurodegenerative disease in which the formation of extracellular aggregates of amyloid beta (Aβ) peptide, fibrillary tangles of intraneuronal tau and microglial activation are major pathological hallmarks. One of the key molecules involved in microglial activation is galectin-3 (gal3), and we demonstrate here for the first time a key role of gal3 in AD pathology. Gal3 was highly upregulated in the brains of AD patients and 5xFAD (familial Alzheimer's disease) mice and found specifically expressed in microglia associated with Aβ plaques. Single-nucleotide polymorphisms in the LGALS3 gene, which encodes gal3, were associated with an increased risk of AD. Gal3 deletion in 5xFAD mice attenuated microglia-associated immune responses, particularly those associated with TLR and TREM2/DAP12 signaling. In vitro data revealed that gal3 was required to fully activate microglia in response to fibrillar Aβ. Gal3 deletion decreased the Aβ burden in 5xFAD mice and improved cognitive behavior. Interestingly, a single intrahippocampal injection of gal3 along with Aβ monomers in WT mice was sufficient to induce the formation of long-lasting (2 months) insoluble Aβ aggregates, which were absent when gal3 was lacking. High-resolution microscopy (stochastic optical reconstruction microscopy) demonstrated close colocalization of gal3 and TREM2 in microglial processes, and a direct interaction was shown by a fluorescence anisotropy assay involving the gal3 carbohydrate recognition domain. Furthermore, gal3 was shown to stimulate TREM2-DAP12 signaling in a reporter cell line. Overall, our data support the view that gal3 inhibition may be a potential pharmacological approach to counteract AD. Erratum in: Acta Neuropathol. 2023 Apr;145(4):509-510
Copyright de los autores.
Keywords: Alzheimer, Enfermedad de - Terapéutica experimental; Alzheimer’s disease; Amyloid aggregation; Galectin-3; Inflammation; Microglia; TREM-2